Smartphone Photography: Empowerment of Online Businessmen in Paciran District, Lamongan Regency through Product Photo Training - Musrifah, Musrifah (Communautaire: Journal of Community Service, 2022)
Online business has become the famous of society lately,especially since the pandemic hit the economic sector. Onlinebusiness has proven to be able to save many householdsfrom economic hardship. One of the online businessstrategies is to upload promotional statuses that displayproduct photos on their social media. The condition ofbuyers and sellers who do not meet physically makes the roleof product photos in online business very important.However, not all online businesses have eye-catchingproduct photos, especially online businesses who sellhandmade products on a household scale. The focus of thisservice focuses on empowering online businesses, especiallythose selling handmade products on a household scale sothat they are able to produce attractive product photos sothat they can exist and compete on social media in particular.This service is in the form of online product photo trainingusing a smartphone. Within ten days, the service participantswere proven to be able to produce quality product photoswith several compositions and angles.